VD_FINDINFO HC / 2010 / 561 vom 26. Juli 2010 - VD Tribunal cantonal (2010)
VIOLENCE CONTRE LES AUTORITÉS, CONSTATATION DES FAITS, APPRÉCIATION DES PREUVES | 285 ch. 1 CP, 411 let. h CPP, 411 let. i CPP